Evaluation of care for elderly women with oncotic pap smear abnormalities in a referral unit - Medeiros, Adna Sandriele Oliveira de Lima; Resende, Vanessa Caroline Pinheiro Martins; de Oliveira , Caio Medeiros; Souza, Nádia Martins de Paula; Souza, Sádia Martins de Paula (Seven Editora, 2024)
Genital infection by the Human Papillomavirus (HPV) is the most frequent sexually transmitted infection in women and its prevalence is associated with risk factors such as: early initiation of sexual life, multiplicity of sexual partners and non-use of barrier methods. Studies show that despite the decrease in the risk of infection in relation to the general age group, a peak is recorded in women aged 65 years, with an increase in the prevalence of HPV. This fact is associated with increased longevity and better conditions of the population, which make them more active, with better quality of life, interests and sexual expressions. Studies addressing HPV infection in elderly women are negligible, although some aspects corroborate the occurrence of a peak in HPV prevalence at 65 years of age. Therefore, investigations that support this foundation are necessary to increase the scope of available information on HPV in this population group. DOI:https://doi.org/10.56238/sevened2024.018-057